A longitudinal uncontrolled study of cerebral gray matter volume in patients receiving natalizumab for multiple sclerosis. (4th May 2017) - Khalid, Fariha; Tauhid, Shahamat; Chua, Alicia S.; Healy, Brian C.; Stankiewicz, James M.; Weiner, Howard L.; Bakshi, Rohit
Abstract : Objective : Brain atrophy in multiple sclerosis (MS) selectively affects gray matter (GM), which is highly relevant to disability and cognitive impairment. We assessed cerebral GM volume (GMV) during one year of natalizumab therapy. Design/methods : Patients with relapsing–remitting ( n = 18) or progressive ( n = 2) MS had MRI ∼1 year apart during natalizumab treatment. At baseline, patients were on natalizumab for (mean ± SD) 16.6 ± 10.9 months with age 38.5 ± 7.4 and disease duration 9.7 ± 4.3 years. Results : At baseline, GMV was 664.0 ± 56.4 ml, Expanded Disability Status Scale (EDSS) score was 2.3 ± 2.0, timed 25-foot walk (T25FW) was 6.1±3.4 s; two patients (10%) had gadolinium (Gd)-enhancing lesions. At follow-up, GMV was 663.9 ± 60.2 mL; EDSS was 2.6 ± 2.1 and T25FW was 5.9 ± 2.9 s. One patient had a mild clinical relapse during the observation period (0.052 annualized relapse rate for the entire cohort). No patients had Gd-enhancing lesions at follow-up. Linear mixed-effect models showed no significant change in annualized GMV [estimated mean change per year 0.338 mL, 95% confidence interval −9.66, 10.34, p = 0.94)], GM fraction ( p = 0.92), whole brain parenchymal fraction ( p = 0.64), T2 lesion load ( p = 0.64), EDSS ( p = 0.26) or T25FW ( p = 0.79). Conclusions : This pilot study shows no GM atrophy during one year of natalizumab MS therapy. We also did not detect any loss of whole brain volume or progression of cerebral T2 hyperintense lesion volume during the observation period. These MRI results paralleled the lack of clinical worsening.